2011
DOI: 10.1136/jnnp-2011-300843
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular changes in prolonged migraine aura in FHM with a novel ATP1A2 gene mutation

Abstract: Although the perfusion state could be different depending on the time course of migraine or the timing of scans in relation to cortical spreading depression, prolonged aura symptoms in this family were frequently associated with hyperperfusion and middle cerebral artery vasodilation. Hyperperfusion tended to occur in the 'predominantly affected hemisphere,' but the mechanism of HMPA awaits further investigations on additional cases of FHM2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 41 publications
4
39
0
Order By: Relevance
“…Imaging FHM patients with prolonged symptoms (lasting 4 to 12 days) on days 1 to 4 most frequently evidenced hyperperfusion in the "predominantly affected hemisphere" contralateral to hemiplegia, although hypoperfusion was also noted. 25,26 The "non-predominantly affected" hemisphere exhibited only hypoperfusion. in 2 patients with signs of acute ischemic stroke who turned out to suffer from FHM, Hansen and colleagues 27 recorded the early phase of the hemiplegic aura using computed tomography with perfusion sequences and MRI.…”
Section: This Review Was Initiated With a Pubmed Search Of The Us Natmentioning
confidence: 99%
“…Imaging FHM patients with prolonged symptoms (lasting 4 to 12 days) on days 1 to 4 most frequently evidenced hyperperfusion in the "predominantly affected hemisphere" contralateral to hemiplegia, although hypoperfusion was also noted. 25,26 The "non-predominantly affected" hemisphere exhibited only hypoperfusion. in 2 patients with signs of acute ischemic stroke who turned out to suffer from FHM, Hansen and colleagues 27 recorded the early phase of the hemiplegic aura using computed tomography with perfusion sequences and MRI.…”
Section: This Review Was Initiated With a Pubmed Search Of The Us Natmentioning
confidence: 99%
“…7 Single-photon emission computed tomography (SPECT) data indicate that clustering of CSD may also develop in hemiplegic migraine, a special subtype of migraine characterized by prolonged aura with motor weakness. 8,9 Nevertheless, to the best of our knowledge, the pathophysiological difference between single and clustering spreading depression/ depolarization has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…Fedak et al reported four pediatric cases of SHM where these flow abnormalities spontaneously resolved within 24 h after hospital presentation [23]. Other authors have reported similar findings [24][25][26]. Sugrue et al described a case wherein evidence of cerebral edema without evidence of infarction was documented in a patient with persistent hemiplegia following headache [27].…”
Section: Sporadic Hemiplegic Migrainementioning
confidence: 72%